Geotechnical earthquake engineering - Towhata, Ikuo (Berlin Springer, 2008)
This title summarises the present knowledge on earthquake hazards and their causative mechanisms, experimental studies on nonlinear complex soil behaviour, an analysis to predict ground behaviour during earthquakes, field studies to determine nature of real ground as input data for analysis, and damage mitigation technologies.
Also available in print version.
Electronic reproduction.
Keywords: Earthquake engineering; Soil dynamics; Soil mechanics; Electronic books